2022
DOI: 10.3390/computation10050074
|View full text |Cite
|
Sign up to set email alerts
|

Regression Machine Learning Models Used to Predict DFT-Computed NMR Parameters of Zeolites

Abstract: Machine learning approaches can drastically decrease the computational time for the predictions of spectroscopic properties in materials, while preserving the quality of the computational approaches. We studied the performance of kernel-ridge regression (KRR) and gradient boosting regressor (GBR) models trained on the isotropic shielding values, computed with density-functional theory (DFT), in a series of different known zeolites containing out-of-frame metal cations or fluorine anion and organic structure-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…More accurate shielding (tensor) predictions can be achieved using, e.g. , Kernel Ridge Regression 54,55 or (equivariant) neural networks. 56,57 However, these ML methods use high-dimensional descriptors, making a physical interpretation of the structure– σ correlation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…More accurate shielding (tensor) predictions can be achieved using, e.g. , Kernel Ridge Regression 54,55 or (equivariant) neural networks. 56,57 However, these ML methods use high-dimensional descriptors, making a physical interpretation of the structure– σ correlation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…31 and commonly being used in learning NMR properties from quantum chemical calculations. 37,[42][43][44][45][46] We use a Laplacian kernel and the local atomic Faber-Christensen-Huang-Lilienfeld (FCHL19 (ref. 13 C and 1 H spectra matching.…”
Section: Chemical Shi Predictionmentioning
confidence: 99%
“…7 Miscelaneous examples, including machine learning of nuclear magnetic shielding modeling Current density, nuclear shielding and magnetizability in a very intriguing molecule of infinitene, resembling the infinity symbol or stretched coronene, were calculated and analyzed by Summa et al 146 Kutateladze et al 147 reported on machine learning-augmented density functional theory (DU8ML) nuclear magnetic resonance computations for high-throughput solution structure validation. Mineva et al 148 used regression machine learning models to predict DFT-calculated NMR parameters of zeolites. Costa et al 149 applied DP4þ and ANN-PRA methodology to determine the relative configuration of a natural product (alpha-bisabol).…”
Section: Nuclear Shielding Calculation In Natural Productsmentioning
confidence: 99%